2015
DOI: 10.1016/j.carpath.2014.08.003
|View full text |Cite
|
Sign up to set email alerts
|

In vitro models of aortic valve calcification: solidifying a system

Abstract: Calcific aortic valve disease (CAVD) affects 25% of people over 65, and the late-stage stenotic state can only be treated with total valve replacement, requiring 85,000 surgeries annually in the US alone [1]. As CAVD is an age-related disease, many of the affected patients are unable to undergo the open-chest surgery that is its only current cure. This challenge motivates the elucidation of the mechanisms involved in calcification, with the eventual goal of alternative preventative and therapeutic strategies. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
57
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(62 citation statements)
references
References 121 publications
4
57
0
Order By: Relevance
“…VICs are important regulators of valve ECM, but pathological VIC activation leads to excessive collagen deposition, a disorganized matrix, and valve fibrosis [6]. Mechanisms contributing to this disease state are still being elucidated, and there are no clinical treatments to slow or reverse valve fibrosis [4].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…VICs are important regulators of valve ECM, but pathological VIC activation leads to excessive collagen deposition, a disorganized matrix, and valve fibrosis [6]. Mechanisms contributing to this disease state are still being elucidated, and there are no clinical treatments to slow or reverse valve fibrosis [4].…”
Section: Discussionmentioning
confidence: 99%
“…The VIC myofibroblast phenotype is characterized by the presence of prominent α-smooth muscle actin (αSMA) stress fibers and associated with increased proliferation, ECM remodeling, and cytokine secretion [2,6]. In vitro culture systems afford an opportunity to study this transition, especially as a function of VIC-matrix interactions and in the absence of the complex signaling milieu that occurs in vivo .…”
Section: Introductionmentioning
confidence: 99%
“…d, e Sheath was retracted to deploy the valve. f Valve deployed potentially utilizing existing in vitro or in vivo models with LDLR gene mutations, hypercholesterolemic diet induction, or traumatic provocation, should be considered [33][34][35][36]. Furthermore, the incorporation of common interventional adjuncts, such as guidewires or balloon catheters, will be essential; many institutions now utilize balloon valvuloplasty prior to TAVR in select cases of severe aortic stenosis [37,38].…”
Section: Discussionmentioning
confidence: 99%
“…19 However, these animal models may not fully share the pathobiology of human valve calcification. It was reported that porcine VICs did not form mineral deposits when treated with osteogenic media with TGF- β 1 20 and became contact-inhibited monolayers, which behave unstably during long-term cell culture.…”
Section: Introductionmentioning
confidence: 99%